Corporations and constitutional guarantees - Foster, Elizabeth (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1990)
Certain constitutional guarantees are now clearly available to corporations, under the Canadian Charter of Human Rights and Freedoms, in the areas of Fundamental Freedoms and Legal Rights. Ambiguous terminology in the provisions dealing with Mobility and Equality Rights leaves the status of corporate applicants uncertain. The rationale of Big M may guarantee constitutional protection to corporations as indirect beneficiaries of rights to which they have no direct access. Whereas in the case of the Canadian Charter, responsability for the clarification of the scope and thereby of the political and social impact of the guarantees is likely to remain with the courts, an alternative solution may be available in Quebec. Clarification and/or reconsideration of the objectives of the Quebec Charter of Human Rights and Freedoms, as they are defined through the identification of its beneficiaries, could take place in the context of general constitutional review.